Regulatory-legal and methodical aspects of social-hygienic monitoring and risk-oriented surveillance model integration - A.Yu. Popova; N.V. Zaitseva; I.V. May; D.A. Kiryanov (Анализ риска здоровью, 2018)
The authors stress in the paper that at a moment when a large-scale administrative reform of control-surveillance activities in the Russian Federation took place there was an efficient tool greatly compatible with control and surveillance activities, a so called social-hygienic monitoring system. When control and surveillance activities and social and hygienic monitoring are brought together, it is a process when mutual integration of both systems takes place; results obtained in one of them give grounds for planning in another. Control and surveillance activities should give precise and targeted recommendations for the social social-hygienic monitoring system for those objects which are to be observed systematically. Both systems accumulate data on which obligatory requirement this or that surveillance object is likely to violate. The monitoring systems allows to make scientifically grounded choice on observation points and monitoring programs development taking all zones influenced by risk sources into account. Measurement results are aimed at validated and precise determination of unacceptable health risk occurrence or threats to human life or health as well as an object causing such threats. But still each systems continues to solve each own tasks attributable only to it. Both systems, social-hygienic monitoring and control and surveillance activates, are becoming dynamic. Monitoring points and observations programs are changing in accordance with surveillance authorities actions and economic entities reactions to such actions. Control and surveillance authorities get another tool which helps to further validate their efficiency over the previous time periods. System management processes are cyclic and have time gaps between specific stages during a year; it causes substantial time expenses which are necessary to obtain optimal parameters. The overall management cycle for one system is equal to 4 years, and for combined systems, 8 years.